European biologic training course for type 2 inflammation by EUFOREA in 2024: key facts and lessons learned - Conti, D. M.; Backer, V.; Fokkens, W.; Gevaert, P.; Peters, A.; Scadding, G. K.; Pavord, I.; Lau, S.; Wechsler, M.; Bertels, X.; Liva, G.; Doulaptsi, M.; et al. (Frontiers in Allergy, 2024)
The European Forum for Research and Education in Allergy and Airways diseases (EUFOREA) organized the first European Biologic Training Course (EBTC) in Brussels on 1st March 2024. The aim of this hybrid EBTC including both face-to-face and web-based participation was to address the educational needs of physicians dealing with asthma and Chronic Rhinosinusitis with Nasal Polyps (CRSwNP) on the clinically relevant aspects of diagnosing and treatment with biologics. EUFOREA is an international non-for-profit organization forming an alliance of all stakeholders dedicated to reducing the prevalence and burden of chronic respiratory diseases through the implementation of optimal patient care via educational, research, and advocacy activities. The inclusive and multidisciplinary approach of EUFOREA was reflected in faculty coming from the paediatric, allergology, pulmonology, and Ear, Nose and Throat (ENT) speciality and from different continents, with more than 250 participants from over 30 countries in the first EBTC. The current report provides a comprehensive overview of key statements made by the faculty of the EBTC 2024, especially focusing on patient selection for a biologic drug, the communication with patients, the onset of biological treatment and the follow-up in routine clinical practice.